Laser‐Assisted Synthesis of Colloidal FeWxOy and Fe/FexOy Nanoparticles in Water and Ethanol. Issue 11 (3rd May 2018) - Lasemi, Niusha; Bomatí Miguel, Oscar; Lahoz, Ruth; Lennikov, Vassili. V.; Pacher, Ulrich; Rentenberger, Christian; Kautek, Wolfgang
Abstract: Homogeneous polycrystalline Fex Oy nanoparticles were generated by ablation of iron targets in water by nanosecond laser pulses at 532 nm. In ethanol, crystalline core‐shell Fe/Fex Oy structures with size medians around 20 nm were produced. The ablation of FeWx Oy targets in water resulted in crystalline hollow shells and homogeneous FeWx Oy nanoparticles. In contrast, amorphous core‐shell FeWx Oy nanoparticles with a median size of 17 nm were produced in ethanol. The size distribution of both the Fex Oy and the FeWx Oy particles showed a slight dependence on fluence and pulse number. This may be related to primary and secondary ablation and modification mechanisms. Abstract : The nature of the target material and the liquid has a strong influence on the composition and structure of nanoparticles synthesized by laser ablation.